Responsibility and Ethics in Simultaneous Interpretation of Films - Sibul, Karin (Vertimo studijos, 2023)
In this article I raise two questions concerning ethics: Was it ethical to interpret in the way that was done in academic film clubs in Soviet Estonia, where Western films that were banned from public screenings in cinemas were simultaneously interpreted in the 1970s and 1980s, and is it ethical to respond to those interpreters’ best efforts in the way the audience responded to my presentation fifty years later? The non-professional interpreting practice in question violates contemporary codes of ethics (accuracy, impartiality, etc.) and goes against current interpreting techniques (condensation, omission, etc.). The interpreters applied creative cross-cultural communication, but was this ethical? This practice ensured accessibility to renowned works of cinematography as without interpretation the screening of those films in the original version might have not taken place. The outcome was shaped by the implicit expectations of the viewers. In 2022, the response to my presentation on this type of film interpreting at a conference was hilarious.
Keywords: simultaneous interpreting of films; history of interpreting; academic film club; ethics; user expectations